Mechanisms involved in follistatin‐induced hypertrophy and increased insulin action in skeletal muscle. Issue 6 (11th August 2019) - Han, Xiuqing; Møller, Lisbeth Liliendal Valbjørn; De Groote, Estelle; Bojsen‐Møller, Kirstine Nyvold; Davey, Jonathan; Henríquez‐Olguin, Carlos; Li, Zhencheng; Knudsen, Jonas Roland; Jensen, Thomas Elbenhardt; Madsbad, Sten; Gregorevic, Paul; Richter, Erik Arne; et al.
Abstract: Background: Skeletal muscle wasting is often associated with insulin resistance. A major regulator of muscle mass is the transforming growth factor β (TGF‐β) superfamily, including activin A, which causes atrophy. TGF‐β superfamily ligands also negatively regulate insulin‐sensitive proteins, but whether this pathway contributes to insulin action remains to be determined. Methods: To elucidate if TGF‐β superfamily ligands regulate insulin action, we used an adeno‐associated virus gene editing approach to overexpress an activin A inhibitor, follistatin (Fst288), in mouse muscle of lean and diet‐induced obese mice. We determined basal and insulin‐stimulated 2‐deoxy‐glucose uptake using isotopic tracers in vivo . Furthermore, to evaluate whether circulating Fst and activin A concentrations are associated with obesity, insulin resistance, and weight loss in humans, we analysed serum from morbidly obese subjects before, 1 week, and 1 year after Roux‐en‐Y gastric bypass (RYGB). Results: Fst288 muscle overexpression markedly increased in vivo insulin‐stimulated (but not basal) glucose uptake (+75%, P < 0.05) and increased protein expression and intracellular insulin signalling of AKT, TBC1D4, PAK1, pyruvate dehydrogenase‐E1α, and p70S6K, while decreasing TBC1D1 signaling ( P < 0.05). Fst288 increased both basal and insulin‐stimulated protein synthesis, but no correlation was observed between the Fst288‐driven hypertrophy and the increase in insulin‐stimulated glucose uptake. Importantly, Fst288 completely normalized muscle glucose uptake in insulin‐resistant diet‐induced obese mice. RYGB surgery doubled circulating Fst and reduced activin A (−24%, P < 0.05) concentration 1 week after surgery before any significant weight loss in morbidly obese normoglycemic patients, while major weight loss after 1 year did not further change the concentrations. Conclusions: We here present evidence that Fst is a potent regulator of insulin action in muscle, and in addition to AKT and p70S6K, we identify TBC1D1, TBC1D4, pyruvate dehydrogenase‐E1α, and PAK1 as Fst targets. Circulating Fst more than doubled post‐RYGB surgery, a treatment that markedly improved insulin sensitivity, suggesting a role for Fst in regulating glycaemic control. These findings demonstrate the therapeutic potential of inhibiting TGF‐β superfamily ligands to improve insulin action and Fst's relevance to muscle wasting‐associated insulin‐resistant conditions in mice and humans.